PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN HARGA DIRI RENDAH SISWA JALUR TEMPATAN SISWA KELAS X SMAN 4 PEKANBARU T.P 2014/2015 - Suherni, Wiwik; Arlizon, Raja; Asyari, Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The title of this research is ?? Effect of Group guidance towards the enhancement of low self esteem of First ? Year local track students of Academic Year 2014/2015 at SMAN 4 Pekanbaru??. The purposes of this research were 1) to know the description of local track students? self esteem before given group guidance service, 2) to know the dynamic description of the group guidance implementation in order to enchacement of low self esteem? , 3) to know the description of students? low self esteem enhancement after given group guidance service, 4) to know how much the difference of local track students? low self esteem enhancement before and after given group guidance service is, 5) to know how much the influence of group guidance towards the enhacement of local track students?low self esteem is. The instrument used in this research was scale self esteem iventori (sei). The subjects of this research were 29 first ? year local track students of academic year 2014/2015 at SMAN 4 Pekanbaru. The sample of this research was 29 students and they were selected by purposive sampling. The description of self esteem before given group guidance was in low category (100%), medium category (0%), and high category (0%). The description of local track students? self esteem enhacement after given group guidance was in lowcategory (0%), medium category (100%), and high category (0%). Based on the result of the calculation of the correlation coefficient between X1 and X2 was 0,46 and the determination coefficient (r2) was 0,21. This means that the contribution of group guidance towards the enhacement of low self esteem was 21%. Therefore, it can be known that ttest was bigger than ttable, (12,6 > 2,021) so that Ha was accepted . So, it means that there was influence of group guidance towards the enhancement of low self esteem of first ? year local track students of academic year 2014/2015 at SMAN 4 Pekanbaru.Keywords : Group guidance, Self Esteem.